Psychological and pedagogical aspects of civil identity andpatriotism formation in a school at the present stage of education - Tamara Gissovna Tuova; Nafset Shumafovna Blyagoz; Fatima Dautovna Teuchezh (Вестник Майкопского государственного технологического университета, 2023)
The problem of a person's civic identity formation accompanies society modernization, and it is especially relevant today, not only for the development of personality traits, but also for the younger generation, who should be active citizens of their state, their homeland. Awareness of an individual to belong to a community of citizens of a certain state, on a general cultural basis, determines civic identity. Due to the fact that students of different ages have different life experiences, they need the help of a teacher when choosing life guidelines. Adolescents do not have well-established social motives, interests and sufficient experience, just as the desire for independence is not always supported by interests and sufficient experience. The requirements of the Federal State Standard state that the basis of civic identity is the basic national values.The purpose of the research is to diagnose the formation of civic identity and patriotism among adolescents and the possible psychological and pedagogical conditions for their formation in the lessons at school, using the example of geography lessons in the course of "Geography of Russia".The research methods used are theoretical and empirical methods, including the study of methodological approaches to understanding the problem of civic identity and patriotism formation; questioning, methods of mathematical statistics.The results of the research have led to the following key conclusions:Methodological approaches of philosophers, teachers and psychologists were used: N.A. Berdyaev, M.S. Kagan, K.D. Ushinsky, V.A. Sukhomlinsky, V.I. Galperin, who studied the spiritual and moral basis of a personality, psychological and spiritual mentality of people, and folk values in education.Analysis of the results of the survey of students of 8-9 grades of MBOU "Maikop Gymnasium No. 22" in the 2021/2022 academic year, the positive results of the pedagogical experiment proved the validity of the proposed methodology for teaching the course of the "Geography of Russia", the effectiveness of psychological and pedagogical conditions in the formation of knowledge of patriotic content, increasing the level of formation of civic identity and moral and patriotic position.